L’enjeu et défis sur l’efficacité de la gestion administrative dans la ville de Kisangani Par - Yinda, Trésor MOKIANGO; Salumu, Fiston WANDJA; Singa, Nathan IUNGBI; Koluwa, Samy Katusi (IJRDO - Journal of Social Science and Humanities Research, 2018)
The promulgation of the constitution of 18 February 2006 in the Democratic Republic of Congo (DRC) as amended to date has resulted in deep institutional reforms by establishing a system of territorial administration that operates at three levels: the central government provinces and decentralized territorial entities; with as vision the impulse of development at the base, that is to say at the local level.Several agents and administrative staff have not yet understood it. That is why this article highlights the attributions and the mode of operation of the decentralized territorial entities as envisaged by the legislative and statutory provisions in force, by raising the stakes, the challenges and consequences of the incomprehension of the system translated by the mismanagement. in the town of Kisangani, particularly in the Makiso commune, both by proposing, finally, solutions for palliative solution to this problem.